(3TaGA GdUOhQs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg hGdMeO efJg hCTcQg hGdTcQ fYeJg (B... (3ebOeI(B: (3deG GbJVJ MceI Gddg GdHGdZI Ndb fhY GdEfSGf HYO Cf de jcf djTZd CQLGA CQVg HGdJSHjM hGdJMejOs
(3BNQgG (B:s
(3BNQgG(B: (3bGd LYdJ aOGc cGf dj Ydjg TjA aGSJbVjJ Ydjg Mbj, abGd CHh YHO Gddg GVQHfj Yfg(B. (3bhd Gddg YR hLd(B: (3jNGahf ShA GdMSGH, CJQGge NGahG Cf jMja Ydjge Ch jXdege hdcf NGahG GdGSJbVGA (B... (3hEdi gfG La eOGO Gdbde HMeO Gddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3GdPQjYI, L (B14: 123s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs